Prevalence of Neuropathic Pain and Related Characteristics in Hidradenitis Suppurativa: A Cross-Sectional Study - Garcovich, Simone (J Clin Med, 2020)
Background: Pain is a core symptom of hidradenitis suppurativa (HS) and is of complex, multifactorial origin. HS patients frequently report typical neuropathic pain qualities, but its prevalence has been poorly described. Methods: In this cross-sectional study, we examine the prevalence of neuropathic pain (NP) component and related pain-characteristics of a hospital-based cohort of patients with symptomatic HS. We administered the pain-DETECT tool (PDQ), a validated screening tool for NP, collecting clinical and patient-reported data on pain, pruritus and pain-management. We obtained 110 complete datasets from symptomatic HS patients (49.1% females; Hurley I (27.3%])–II (45.5%)–III (27.3%)). According to the PDQ tool, 30% of patients were classified with a high probability (>90%) of neuropathic pain (LNP). LNP status was significantly associated with increased pain severity, disease activity, pruritus intensity and use of pain medication. Regression analysis showed a significant impact of the PDQ score on patient-reported outcomes, including pain severity and the dimensions of activity and affective pain interference. HS patients may present a mixed chronic pain phenotype with a neuropathic component, thus requiring additional pain-assessments. A multi-modal approach to pain management, in combination with disease-specific treatment, should be implemented in future interventional studies.